Evaluation of Retinopathy Severity According to the Premature Stage in Premature Retinopathy - Gülistan Oyur; Leyla Hazar; Esra Vural; Yakup Acet; Oğuz Celik (Van Tıp Dergisi, 2020)
INTRODUCTION: The aim of this study is to analyze the relationship between the stage of prematurity and retinopathy severity by analyzing the results of premature retinopathy (PR) screening. METHODS: In state Hospital 862 eyes of 431 cases who were admitted between June 2017 and September 2018 were evaluated retrospectively. Cases were classified according to gestational ages and birth weights. The cases were divided into advanced, intermediate and late premature. The relationship between the severity of retinopathy and the degree of premature and multiple births was evaluated RESULTS: Two hundred thirty four (54.3%) of the cases were female and 197 (45.7%) were male. Birth weeks were 23 to 36 weeks (31.9 +- 2.77), and birth weights were 510-3500 gr (1746 +- 476). PR was detected in 137 (31.8%) of the cases at any stage, and no sign of PR was found in 294 (68.2%) cases. Stage 1 PR was detected in 80 cases (58.4%), stage 2 PR in 42 cases (30.7%), stage 3 PR in 13 cases (9.5%), and stage 4 PR in 2 cases (1.5%). The mean birth weight and gestational week were statistically significantly lower in patients with PR at any stage (p <0.05). Stage 3 and Stage 4 PR were detected in 6 (%4,32) cases with a gestational age of >32 weeks. No significant relationship was found between multiple births and PR. (P = 0.908) DISCUSSION AND CONCLUSION: It should always be considered that there may be advanced stage PR in moderate and late premature.